Impact of migraine attacks on the blood-brain barrier - Gao, Hong-Mei; Li, Le; Zhang, Ke-Ling; Chen, Xu-Hui; Tian, Shu-Qing; Zhang, Zhong-Ling (Chinese medical journal, 2010)
Background Cortical spreading depression can cause migraine attack, and up-regulate matrix metalloproteinase-9 （MMP-9） expression in animal. This study aimed to determine the impact on the structure and function of the blood-brain barrier by measuring plasma MMP-9 levels in patients at the acute and late stages of migraine attacks in order to elucidate the pathological mechanisms involved. Methods We recruited a case-control cohort of 38 adult migraine patients and 20 age- and gender-matched healthy control subjects. Five milliliter blood samples were collected at the acute and late stages of migraine （days 1-7）, and also from the control subjects. Solid phase double antibody sandwich enzyme-linked immunosorbent assay was used to determine plasma MMP-9 levels. Statistical analysis was performed using the SAS version 9.1. Results Initial plasma MMP-9 levels of migraine patients were significantly higher than those of controls （（12.612±0.016） μg/L vs. （6.069±0.023）μg/L, respectively, P 〈0.05）. High MMP-9 expression was observed during days 1-6 of migraine attacks, with highest expression occurring on day 3 （（17.524±0.035） μg/L）. During attacks, MMP-9 levels were similar in migraine patients with and without aura （P 〉0.05）; in addition, levels were not correlated with degree of headache pain （P 〉0.05）. Conclusions We hypothesize that migraine could lead to increased plasma MMP-9 levels resulting in blood-brain barrier damage. MMP-9 levels increase during days 1-6 of migraine attacks, peaking on day 3. Therefore, MMP-9 could be used as a biological marker to guide treatment of migraine attacks.